Neutral gas and the escape of ionizing radiation: Lessons from the low-redshift Green Peas. Issue Volume 15:Issue S352(2019) (June 2019) - Jaskot, Anne; McKinney, Jed; Dowd, Tara; Oey, Sally; Yun, Min; Scarlata, Claudia; Lowenthal, James
Abstract: How galaxies reionized the universe remains an open question, but we can gain insights from the low-redshift Green Pea galaxies, one of the only known populations of Lyman continuum (LyC) emitters. Using VLA H i 21 cm observations and HST UV spectra of Green Peas, we investigate how neutral gas content and geometry influence LyC and Lyα escape. Our results suggest that LyC Emitters may have high ratios of star formation rate to H i mass. Low gas covering fractions are common among the population, but not all sightlines are optically thin. Based on the observed relationship between high ionization parameters, low metallicities, and narrow Lyα profiles, we propose that weak stellar feedback at low metallicities results in a gas geometry of dense clumps within a low-density medium, which facilitates Lyα and LyC escape. We address the implications of these results for identifying LyC emitters at high redshift with JWST and ALMA.